(3GdeGdjI hGdJLGQI GdOhdjI (B:s (3edNUGJ GdeMGVQGJ hJeGQjf efgLjI (B/s - (3RGjQj, HdbGSes ((3GdLRGFQ(B: s (3GdfTQ GdLOjO GdLGeYj(B, s, 2016)
(3aj gPG GdcJGH GdaUd GdGhd (B: (3fXQjI GdJLGQI GdOhdjI GdeDTQGJ GdGMUGFjI GdeQJHWI HGdJLGQI GdOhdjI , GdJNUU GdOhdj MSH GdfeGPL GdcdGScjI , JMOjK GdfXQjGJ GdcdGScjI (B((3LGfH GdYQV (B)(3, efMfjGJ GdShGA GdeLJeYjI , eYOd GdJHGOd GdOhdj , fXQjI gjcTQ (B_(3Chdjf GdGfJGL , Gdfeh hGdJLGQI GdOhdjI GdaUd GdKGfj GdSjGSIGJ GdJLGQjI hfXQjI GdJcGed GdGbJUGOj GdSjGSI GdJLGQjI ,GdJcGed GdGbJUGOjs
Keywords: (3GdGbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdYdGbGJ GdGbJUGOjI GdOhdjIs; (3GdeGdjI GdOhdjIs